The Impact of Food Self-Sufficiency on National Economy in West Africa: Case of the Republic of Guinea - Shaikh, Dr. Junaid M.; Kourouma, Kandas; Diallo, Aissata (Archives of Business Research, 2022)
This study examines in the impact of food selficiency on national economy in West Africa particular case Guinea, the major problems of populations needs is food selficiency in Africa. However ; to achieve the self-sufficiency the authorities encourage its production to provide income for Producer, for domestic consumption and for a net exporting country. Local food production remains highly competitive with imported food. In addition, food insecurity across the country is a major development issue that threatens health, productivity and often the survival of the population. This study helps overcome developmental problems due to food selficiency, therefore, the main objective of this study is to analyze the impact of food production in the country and to examine more closely the relationship between food production and national economy on the domestic market. The study used a linear logarithmic model with the exchange rate output as a dependent variable and the food import, inflation rate, umemployment rate, interest rate and population growth. The current results found that imported food is positive sign, supporting the argument that imports products as viable income-generating activity. The self-sufficiency rate is 94%, with strong imports from imports countries, any exports. However, in order to control an national economic income and till increase agriculture production, the government should be able to purchase the food crops production from populations employment to the farmers and then sell them to projects in place for reduce food importation between international, regional and national domestic production along the markets. The development of the national economy Sectors and reduction of poverty and hunger, in particulary growing selficiency of food Security in Guinea.